2022
DOI: 10.1007/s12325-022-02067-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Guided Prescription of Azathioprine Reduces the Incidence of Adverse Drug Reactions in TPMT Intermediate Metabolizers to a Similar Incidence as Normal Metabolizers

Abstract: Introduction: Thiopurine drugs are purine nucleoside analogues used for treatment of different immune-related conditions. To date, different studies highlighted the importance of thiopurine methyltransferase (TPMT) genotyping in patients who initiate treatment with thiopurines to make an adequate dose adjustment. We aimed to investigate the influence of TPMT phenotype, concomitant treatments, and demographic characteristics on the incidence of A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Genotyping routinely in patients with CVS for CYP2C19 and CYP2D6 has the potential to tailor management at the outset and optimize outcomes in CVS. This is akin to testing for the thiopurine S‐methyltransferase (TPMT) in inflammatory bowel disease (IBD) 13,27 . TPMT metabolizes thiopurine drugs, such as azathioprine and 6‐mercaptopurine, which are commonly used in the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping routinely in patients with CVS for CYP2C19 and CYP2D6 has the potential to tailor management at the outset and optimize outcomes in CVS. This is akin to testing for the thiopurine S‐methyltransferase (TPMT) in inflammatory bowel disease (IBD) 13,27 . TPMT metabolizes thiopurine drugs, such as azathioprine and 6‐mercaptopurine, which are commonly used in the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with other areas like IBD where pharmacogenomics is utilized routinely to manage and individualize care such as in testing for TPMT genotype prior to initiating azathioprine. 13 The utility of pharmacogenomics in objectively predicting the risk of ADRs and optimizing treatment with AT can allow for personalized management of patients with CVS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the latter population needs more doses to resist rapid intermediate metabolite inactivation (Yates et al, 1997). Studies have shown that TPMT genotyping and dose adjustment before using AZA can reduce the incidence of ADR in intermediate metabolites to a level similar to normal metabolism in the Spanish population (Casajus et al, 2022).…”
Section: Mycophenolate Mofetil and Azathioprinementioning
confidence: 99%
“…However, its therapeutic usage has been limited due to its dose-dependent adverse effects like hepatotoxicity, gastric intolerance, and bone marrow toxicity (Ana Casajús et al 2022). Especially these adverse effects are more pronounced in thiopurine methyltransferase (TPMT) intermediate metabolizers (IMs) (Ana Casajús et al 2022). Drug withdrawal is required in up to 9% of the IBD patients due to hepatotoxicity concerns (Labidi et al 2020).…”
Section: Introductionmentioning
confidence: 99%